Estudio de factibilidad para la creación de una caja de ahorro para la Compañía de transporte comercial de carga pesada “Rogelio Macas y Asociados S.A”, parroquia Valle Hermoso - Provincia Santo Domingo de los Tsáchilas - Ambuludi Cabrera, Mercy Soledad (2019)
The purpose of this research work, is to provide information that determines the feasibility of creating a savings bank in the Company, which aims to facilitate financing through credits, as well as promoting a culture of savings; since within the parish there is no financial institution that provides financial services. The services to offer will be based on the values of solidarity and mutual trust that allow to improve the activities of transport service and the socioeconomic development of each member. For the development of the project, the market study was used, technical, administrative-legal, financial economic and financial evaluation. In order to fulfill the objectives of the project, methods such as inductive, deductive, analytical and techniques such as direct observation, collection of bibliography and survey were used, which allowed obtaining clear and truthful information. In addition, the literature review was structured, which consisted of basic concepts that served as a guide for the development of this thesis. In order to comply with the first objective referring to the market study, surveys were applied to the Company's members, with which the degree of acceptance of the savings bank and of the financial products and services to be offered was determined, as well as the savings and credit services whose interest rates, both active and passive, are fixed according to the referential rates of the Central Bank of Ecuador. With this study it was possible to establish the potential, real, effective and unsatisfied demand. In the technical study was determined the exact location where the project will be developed, the ideal place will be on the second floor of the company's facilities, in the size of the same was calculated the capacity of the institution to grant credits obtained from the contribution of the obligatory saving of the members, also established the necessary requirements for the installation and operation of the savings box, then proceeded to prepare the distribution of the plant by a simple design that fits the needs of the institution and also describes the flow of grams for the different processes to be performed. With regard to the administrative-legal study, the requirements for establishing a savings box were detailed, and the functional and structural structure that the box will present, its legal basis and the statutes that will govern it, was also designed The Manual of functions determining the activities and responsibilities that the personnel will have to fulfil for the efficient operation of the institution. In the third objective that is the economic study the initial investment required to implement the project was determined, taking into account fixed, deferred and current assets with their respective depreciations and amortizations resulting in an investment $3,518.23, the financing of which will be fully obtained from the members own resources. With the financial evaluation confirms the viability of the thesis project, obtaining the following values for the financial indicators: Net Present Value of $22.069,54, Minimum Acceptable Rate of Return of 5.99%, Internal Rate of Return of 55%, Benefit-Cost Ratio of $1.90 and the Recovery Period of the investment is 3 years 4 months. Finally, it was contributed with the relevant conclusions and recommendations, based on the results obtained in the different studies carried out.